2016
DOI: 10.1016/j.jfda.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of Caralluma fimbriata against high-fat diet-induced oxidative stress in Wistar rats

Abstract: The current study was designed to evaluate the renoprotective effect of hydro-alcoholic extract of Caralluma fimbriata (CFE) against high-fat diet-induced oxidative stress in Wistar rats. Male Wistar rats were randomly divided into five groups: control (C), control treated with CFE (C + CFE), high-fat diet fed (HFD), high-fat diet fed treated with CFE (HFD + CFE), and high-fat diet fed treated with metformin (HFD + metformin). CFE was orally administered (200 mg/kg body weight) to Groups C + CFE and HFD + CFE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…The lower activities of SOD and glutathione peroxidase (GPx) showed in obesity compared to a healthy condition and was accompanied by higher malondialdehyde (MDA, as a lipid peroxidation marker) level. [42][43][44] Additionally, high expression of nitric oxide (NO) showed in OA patients and as a proinflammatory mediator, it positively correlated with OA development. 45 In many cases, osteoarthritis is accompanied by joint swelling and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The lower activities of SOD and glutathione peroxidase (GPx) showed in obesity compared to a healthy condition and was accompanied by higher malondialdehyde (MDA, as a lipid peroxidation marker) level. [42][43][44] Additionally, high expression of nitric oxide (NO) showed in OA patients and as a proinflammatory mediator, it positively correlated with OA development. 45 In many cases, osteoarthritis is accompanied by joint swelling and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the plant C. tuberculata also contains potential secondary metabolite molecules [41]. Recently, Gujjala et al [42] showed an appreciable amount of polyphenolic compounds in C. fimbriata followed by saponins and flavonoids.…”
Section: Total Phenol and Flavonoid Contentsmentioning
confidence: 99%
“…[50] Caralluma fimbriata A study on quantitative and qualitative analysis of phytochemical as well as nutritional analysis of the aqueous extract of C. fimbriata was carried out by Padwal et al [51] C. fimbriata extract was proved to be very useful to prevent and manage the oxidative stress in kidneys, based on the evaluation of renoprotective effect of its aqueous alcohol extracts on Wistar rats. [52] Ethanolic extracts of C. fimbriata were found to possess a significant antimutagenicity as these extracts inhibited the reversion created by direct mutagens such as hydroxylamine, ethidium bromide, and sodium azide. [53] S. typhimurium was used in these studies for determination of antimutagenicity.…”
Section: Caralluma Europaeamentioning
confidence: 99%
“…fimbriata Antioxidant capacity [31] Antiadipogenesis [100] Antiproliferative properties [67] Anthelmintic [34] Caralluma adscendens var. Gracilis Antioxidant, antimicrobial, and cytotoxic [101] Caralluma arabica Antioxidant [38] Antioxidant and lipoxygenase inhibitory [39] Antigastric ulcer and cytoprotective [102] Antinociceptive and anti-inflammatory [20] Antihyperglycemic [103] Caralluma attenuata Anthelminthic and antitubercular [40] Antidiabetic [104] Cytotoxic [68] Antidiabetogenic and antioxidant [41] Hypoglycemic [42] Hyperglycemic [105] Antihyperglycemic [43] Anti-inflammatory and antinociceptive [21] Caralluma cicatricose Hepatoprotective [44] Caralluma dalzielii Ameliorative effect [45] Analgesic and anti-inflammatory [46] Antidiabetic [106] Caralluma diffusa Cytotoxic [68] Caralluma edulis Antioxidant [47] Antidiabetic [48] Antioxidant [107] Caralluma fimbriata Antimutagenic [53] Renoprotective [52] Antimicrobial [54]…”
Section: Name Of the Plant Biological Activity Referencesmentioning
confidence: 99%